If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 3x + 0 Reorder the terms: 4 = 0 + 3x Remove the zero: 4 = 3x Solving 4 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 4 + -3x = 0 Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333
| (3x^3+4x^2-2x+1)+(x^4-x^3+5x^2+2x+3)=0 | | 2(-3n)=3(2n) | | (1x+4)= | | (4abc/3x)÷(6ab2/10xy) | | 2/3(42)-6 | | -24+8y=0 | | 9x+60x+100=0 | | xsquared+18x+50=9 | | 2x+5=10x+35 | | 3(1.25)+8y=-1 | | 41=21-2h | | A+15B-A+5B= | | .5x^2+.5x-15=0 | | 3+11=-2(9x-7) | | (x-2)(x+7)=y | | b/12=-144 | | 1/2(a)=11 | | 4(-1)-7y=-8 | | (x+2)ft= | | c+3+5=c+8 | | 486*2= | | 5x+9=s-23 | | 9z^2+12z-4= | | 4(5x-2)+8=14 | | 0+2+x(x)=38 | | 9(1.35)-2y=13 | | 7m^2+46m=-24 | | N-2.7=5.6 | | 3(-r-1)=4 | | z^2-14x=-40 | | 30=a+(2a+3)+(a+7) | | 3(2x+5)=4x+9 |